Antimicrobial stewardship in equine practice. Issue 7 (25th June 2019) - Raidal, SL
Abstract : Antimicrobial stewardship involves the judicious use of antimicrobials balanced against the requirement to treat the presenting clinical condition. The same mandate and principles as discussed in human medicine and other veterinary disciplines are relevant to equine practice. This brief review will focus on available resources for equine practitioners, emerging perspectives on antimicrobial use and stewardship, and opportunities for more effective antimicrobial use in equine practice. There is a need for improved client education, availability of faster and more accurate techniques for identification and sensitivity testing of bacterial pathogens, and the development of novel agents.